Corporate Social Responsibility, Knowledge of COVID-19, and Risk Perception in International Tourism Enterprises - KHASAWNEH, Mohammad; AL NAJDAWI, Bashar M.; SHATNAWI, Hakam S.; ABABNEH, Samer Fandi (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
The goal of this research was to determine if corporate social responsibility, risk perceptions, and understanding of COVID-19 of international tourism enterprises had an impact on Jordanian travelers’ decisions about international tourist products. Questionnaire (self-reporting) was created and distributed to 321 participants, with 311 valid replies being evaluated for statistical analysis. The results of the multiple linear regression show that risk perception, COVID-19 knowledge perception, and international tourism enterprises' corporate social responsibility are major determinants of attitude toward and behavioral intention. Nevertheless, the limited sample size raises the question of generalizability, which should be examined in more depth in future research. The influence of international tourism businesses on travelers’ decision-making by the majority of respondents suggests that such international tourist businesses have a lot of room to grow in the future. The difficulty is to ensure that it continues to match tourism's expectations, resulting in an increase in international tourist business visitors. This research is advanced since it contains information on worldwide tourism businesses, particularly in Jordan. The tourism industry will benefit from the main aspects identified.